NUTRITION EDUCATION THROUGH THE KADERKU SAHABATKU AND NGOCEH PROGAM AT KEMLOKOLEGI VILLAGE, BARON DISTRICT, NGANJUK REGENCY YEAR 2020 - Fatmawati, Zeny; Fatmawati, Elis; Sari, Wahyu Anjas; ., Supiani; Sukamti, Eni (PRIMA WIYATA HEALTH, 2021)
Toddler period is a critical period to get quality human resources and is a growth spurt period where optimal brain growth and development occurs. If the problem of nutritional disorders in toddlers is left unchecked, it will be fatal, Indonesia will lose the next generation of quality(loss generation). The problem of malnutrition in toddlers has been around for a long time and has not been resolved.. The purpose of this activity is expected to be able to reduce morbidity and mortality rates for infants and toddlers in general as well as increase the knowledge of mothers under five regarding the importance of early detection of nutritional problems under five and balanced nutrition in infants in particular in Kemlokolegi Village, Baron District, Nganjuk Regency.The Kaderku Sahabatku and NGOCEH program is a cadre formation program that functions to assist mothers of toddlers in monitoring the growth and development of toddlers and nutritional problems, while the ngoceh program, which is an acronym for Smart and Healthy Chat, is carried out in the toddler class and the formation of nutritional cadres through the cadre program my best friend in Kemlokolegi Village, Baron District, Nganjuk Regency which contains health education activities related to nutritional problems in toddlers which includes education about the benefits of early detection of toddler growth and development and balanced nutrition in toddlers to prevent stunting.The method used in this activity is to provide education about the benefits of early detection of growth and development and balanced nutrition in toddlersThere is an increase in the skills of cadres in conducting health education in mothers with toddlers. There is an increase in mother's motivation to give exclusive breastfeeding, monitoring growth and development of toddlers, balanced nutrition for toddlers. The activities of this mother group are expected to run regularly and sustainably. The implementation of activities is expected to be carried out independently by the community.